2013
DOI: 10.1016/j.aca.2013.09.048
|View full text |Cite
|
Sign up to set email alerts
|

On-line monitoring of food fermentation processes using electronic noses and electronic tongues: A review

Abstract: After a brief description of the fundamentals of both types of devices, the different approaches are critically commented, their strengths and weaknesses being highlighted. Finally, future trends in this field are also mentioned in the last section of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 42 publications
(37 reference statements)
0
68
0
3
Order By: Relevance
“…Similar to E-nose, E-tongue is another intelligent machine system designed to detect complex taste sensations [19]. Previous reports have revealed that the E-tongue possesses sensitivity capability for analyzing and discriminating between various liquid agents, such as wine, honey and tea, and plant or herbal extracts [12,13,18].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to E-nose, E-tongue is another intelligent machine system designed to detect complex taste sensations [19]. Previous reports have revealed that the E-tongue possesses sensitivity capability for analyzing and discriminating between various liquid agents, such as wine, honey and tea, and plant or herbal extracts [12,13,18].…”
Section: Discussionmentioning
confidence: 99%
“…The principle of e-tongue was based on the nature of a potentiometric sensor. It is a non-specific sensing, or it has a low selectivity for chemicals [7]. It is very interesting because the cross-sensitivity of the various components in the solution of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a pattern recognition and multivariate methods should be used to interpret the complex signals of the sensor array. It will be used to predict the value of qualitative and quantitative parameters of the pattern [5], [7], [8]. The sensor of ion selective electrode is made of a membrane which has active ingredients, namely lipids and plasticizer or polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Some sensors, including biomass probe, dissolved oxygen probe, extracellular oxidoreduction potential probe, and gas monitors, are used in fermentation to monitor cell growth, assess aerobic metabolism, estimate NAD + /NADH + ratio, and measure gases (e.g., CO 2 , CH 4 and H 2 ), respectively [4].In addition, biochemical analysers connected to auto-samplers are used for online monitoring of multiple metabolites. Different from discrete sensors, the MS based chemical multisensory systems, named as electronic noses and electronic tongues [5], have been used in both qualitative recognition of multi-component media and quantitative analysis of component concentrations in wine production. With dynamic metabolite data collected using in situ probes and auto-samplers, mathematic modelling can be applied to achieve precise nutrients feed and harvest time in fedbatch fermentation.…”
Section: Introductionmentioning
confidence: 99%